The Nexus of Professional Commitment and Instructional Quality - Joy Aranas Boquida; Nhelbourne K. Mohammad (The Indonesian Institute of Science and Technology Research, 2026)
A quantitative descriptive-correlational design was employed with 1,579 randomly selected public elementary school teachers from the Zamboanga del Norte Division in the Philippines. Professional commitment was measured using an adaptation of Meyer and Allen's (1991) Three-Component Model, while instructional quality was assessed using the Three Basic Dimensions framework (Klieme et al., 2009; Praetorius et al., 2018). Data were analyzed using Pearson's correlation coefficient. Results revealed very high levels of both professional commitment (M=4.23, SD=0.78) and instructional quality (M=4.26, SD=0.78). Normative commitment (M=4.33) and student support (M=4.34) emerged as the strongest respective dimensions. A significant, strong positive correlation was found between the two variables (r=0.68, p<0.001). The study provides empirical evidence that teachers' sense of moral obligation and emotional attachment to the profession is strongly associated with enhanced classroom practices. Findings offer actionable insights for school leadership and targeted professional development in cognitively activating instruction.